Respon Pertumbuhan Tanaman Kedelai (Glycine max L) Varietas Dega Terhadap Pupuk Kompos Ayam Dibandingkan Pemberian Pupuk NPK - Sani Simanjuntak, Budi Herman; Hutapea, Sumihar (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
Soybeans (Glycine max L.) are a strategic food commodity, but their productivity is still low due to declining soil fertility and excessive use of inorganic fertilizers. This study aims to compare the effect of the application of chicken manure and NPK fertilizer on the growth and yield of soybean plants of the Dega variety on marginal land. The research was carried out using a factorial Group Random Design (RAK) with two treatment factors: the type of fertilizer and the application dose, and three replicates. The observed parameters included plant height, number of leaves, number of pods, weight of seeds per plant, and weight of 100 seeds. The results of the study showed that chicken manure had a better influence on vegetative and generative growth than NPK fertilizer. Chicken compost improves soil quality, nutrient absorption efficiency, and microorganism activity. Although NPK fertilizers show a rapid initial response, the long-term advantages of organic fertilizers are more dominant. Therefore, fertilization based on chicken manure is recommended as an environmentally friendly and sustainable soybean cultivation strategy.